2023
DOI: 10.3390/w15061216
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Quality and Health Risk Assessment Using Indexing Approaches, Multivariate Statistical Analysis, Artificial Neural Networks, and GIS Techniques in El Kharga Oasis, Egypt

Abstract: The assessment and prediction of water quality are important aspects of water resource management. Therefore, the groundwater (GW) quality of the Nubian Sandstone Aquifer (NSSA) in El Kharga Oasis was evaluated using indexing approaches, such as the drinking water quality index (DWQI) and health index (HI), supported with multivariate analysis, artificial neural network (ANN) models, and geographic information system (GIS) techniques. For this, physical and chemical parameters were measured for 140 GW wells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…The solution of the system of Equation ( 9) is that K = 4.9522 × 10 −4 m −2 ; B = 9.007 × 10 −3 [-]. Thus, the static transfer coefficient of an object can be written as Equation (10):…”
Section: Study Of the Characteristics Of The Hydrogeological Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution of the system of Equation ( 9) is that K = 4.9522 × 10 −4 m −2 ; B = 9.007 × 10 −3 [-]. Thus, the static transfer coefficient of an object can be written as Equation (10):…”
Section: Study Of the Characteristics Of The Hydrogeological Processmentioning
confidence: 99%
“…The static transfer coefficient of the object is written by Equation (10). The effect of production wells pumping rate on lowering of the level in i-th production well in accordance with [42] can be represented as Equation (12):…”
Section: Determination Of the Optimal Number Of Production Wellsmentioning
confidence: 99%
“…A principal component analysis was performed using nine parameters: conductivity, pH, Cl − , Mg 2+ , Ca 2+ , Na + , SO 4 2− , K + , and HCO 3 − [34,35]. The results (Figure 5a) showed that the first two axes, F1 and F2, explained 80.94% of the overall variance in the water samples.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Heavy metals can enter the human body through various pathways, including oral consumption, dermal contact, and inhalation 11 13 . These contaminants can be found in drinking water sources, such as surface water and groundwater 14 , 15 , vegetables, and air 16 . Metals in the environment can be attributed to industrial, agricultural, domestic, medical, and technological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Effective methods for evaluating the environmental and human health risks associated with heavy metals include the heavy metal pollution index (HPI), metal index (MI), hazard quotient (HQ), hazard index (HI), and carcinogenic risk (CR), integrated with Monte Carlo simulation 2 4 , 9 , 16 – 20 . Furthermore, cluster analysis and principal component analysis (PCA) are valuable tools for classifying the sources of heavy metals and understanding hydrochemical processes in surface water and groundwater 14 , 21 23 . Contaminated water resources pose severe threats to humans and animals, giving rise to major biological and chemical concerns.…”
Section: Introductionmentioning
confidence: 99%